Cross mating studies among five fruit fly parasitoid populations: Potential biological control implications for tephritid pests - Billah, M.K.; Kimani-Njogu, S.W.; Wharton, R.A.; Overholt, W.A.; Wilson, D.D.; Cobblah, M.A. (BioControl, 2008)
The reproductive compatibility between four different species/populations of the tephritid parasitoid Psyttalia (Walker) species from Kenya and individuals of the morphologically identical Psyttalia concolor (Szépligeti) (Hymenoptera: Braconidae) from a laboratory culture in Italy used in augmentative biological control of olive fly, Bactrocera oleae (Gmelin) (Diptera: Tephritidae) was assessed through cross mating tests using single-pair and group mating methods. Reciprocal crosses among the species resulted in the production of viable offsprings up to the second generation. In spite of the successful production of viable offspring in the laboratory, Psyttalia species are known to have specific host fruit and/or host fly preferences and populations/species may be isolated in one way or the other. However, it is not known whether these populations/species interbreed in the field. We discuss the ability of these parasitoids to interbreed and the potential effects of that on their use as biological control agents, especially in environments where other closely related species are present or in situations where multiple parasitoid introductions are intended. © 2007 International Organization for Biological Control (IOBC).
Keywords: Augmentative; Biological control; Cross mating; Parasitoids; Psyttalia concolor; Reproductive compatibility; Tephritids; Viable offspring